2016
DOI: 10.1371/journal.pone.0156860
|View full text |Cite
|
Sign up to set email alerts
|

Association between FGF23, α-Klotho, and Cardiac Abnormalities among Patients with Various Chronic Kidney Disease Stages

Abstract: BackgroundSeveral experimental studies have demonstrated that fibroblast growth factor 23 (FGF23) may induce myocardial hypertrophy via pathways independent of α-Klotho, its co-factor in the induction of phosphaturia. On the other hand, few studies have clearly demonstrated the relationship between FGF23 level and left ventricular hypertrophy among subjects without chronic kidney disease (CKD; i.e., CKD stage G1 or G2).PurposeTo investigate the data from 903 patients admitted to the cardiology department with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 45 publications
2
26
3
Order By: Relevance
“…In this study, we found no significant association between higher FGF‐23 and HFrEF events, while previous studies suggested an association of higher FGF‐23 concentrations with lower LVEF 42, 43, 44. However, these studies showed very modest association with reduced EF.…”
Section: Discussioncontrasting
confidence: 94%
“…In this study, we found no significant association between higher FGF‐23 and HFrEF events, while previous studies suggested an association of higher FGF‐23 concentrations with lower LVEF 42, 43, 44. However, these studies showed very modest association with reduced EF.…”
Section: Discussioncontrasting
confidence: 94%
“…EDV is the amount of blood in the ventricles just before systole and if it increases then eventually may cause LVH, pulmonary congestion and edema. An association between FGF23 and cardiac hypertrophy and systolic dysfunction has been observed among patients without CKD as well as those with CKD after multivariate adjustment [36]. However, present study did not reveal direct association of FGF-23 with LV function, improvement in LV function in terms of reduction in EDV was observed at six month of follow-up of the study where patients were monitored for P levels and for its control.…”
Section: Fgf-23 and Hyperphosphatemia In Dialysis Dependent Chronic Kcontrasting
confidence: 78%
“…[14][15][16][17][18] In addition, between women and men, not only mean SUA levels, but also the SUA threshold at which cardiovascular or metabolic syndrome-associated risks might increase, may vary; 19) therefore, we should analyze the data for each gender separately. In addition, the strength of the association between SUA and certain cardiac abnormalities might differ between women and men.…”
Section: Editorial P467mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Editorial p. 467 To assess whether serum SUA is associated with cardiac hypertrophy and heart failure, 12) we may have to take various possible confounders into account, such as estimated glomerular filtration rate (eGFR), phosphate, 13) and the recently identified phosphaturic hormone fibroblast growth factor 23 (FGF23) that might directly induce hypertrophy of cardiomyocytes. [14][15][16][17][18] In addition, between women and men, not only mean SUA levels, but also the SUA threshold at which cardiovascular or metabolic syndrome-associated risks might increase, may vary; 19) therefore, we should analyze the data for each gender separately. In addition, the strength of the association between SUA and certain cardiac abnormalities might differ between women and men.…”
mentioning
confidence: 99%